Hydrocarbon seepage in the deep seabed links subsurface and seafloor biospheres - Chakraborty, Anirban; Ruff, S. Emil; Dong, Xiyang; Ellefson, Emily D.; Li, Carmen; Brooks, James M.; McBee, Jayme; Bernard, Bernie B.; Hubert, Casey R. J. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Marine cold seeps transmit fluids between the subseafloor and seafloor biospheres through upward migration of hydrocarbons that originate in deep sediment layers. It remains unclear how geofluids influence the composition of the seabed microbiome and if they transport deep subsurface life up to the surface. Here we analyzed 172 marine surficial sediments from the deep-water Eastern Gulf of Mexico to assess whether hydrocarbon fluid migration is a mechanism for upward microbial dispersal. While 132 of these sediments contained migrated liquid hydrocarbons, evidence of continuous advective transport of thermogenic alkane gases was observed in 11 sediments. Gas seeps harbored distinct microbial communities featuring bacteria and archaea that are well-known inhabitants of deep biosphere sediments. Specifically, 25 distinct sequence variants within the uncultivated bacterial phyla Atribacteria and Aminicenantes and the archaeal order Thermoprofundales occurred in significantly greater relative sequence abundance along with well-known seep-colonizing members of the bacterial genus Sulfurovum, in the gas-positive sediments. Metabolic predictions guided by metagenome-assembled genomes suggested these organisms are anaerobic heterotrophs capable of nonrespiratory breakdown of organic matter, likely enabling them to inhabit energy-limited deep subseafloor ecosystems. These results point to petroleum geofluids as a vector for the advection-assisted upward dispersal of deep biosphere microbes from subsurface to surface environments, shaping the microbiome of cold seep sediments and providing a general mechanism for the maintenance of microbial diversity in the deep sea.